2016
DOI: 10.1097/coh.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

HIV replication

Abstract: HIV has evolved sophisticated but imperfect mechanisms to evade and counteract innate sensing. Whether virus-induced immune activation represents merely a suboptimal adaptation of HIV to its human host or even facilitates HIV replication, for example by increasing the number of viral target cells, remains to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 103 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…For HIV, recent studies suggest that such newly transcribed HIV RNA can be differentiated from cellular RNAs by its high degree of secondary structure, including stem-loops or panhandles and other modifications. Therefore, HIV RNA can be differentially sensed by RIGI in the 5= and 3= untranslated regions, including the TAR stem-loop, which are likely to be recognized by RIGI and are probably more exposed in monomers than dimers (46,47). Solis et al (30) showed that both purified monomeric and, to a lesser extent, dimeric genomic RNA (which is transcribed from cDNA and exposed in the cytoplasm prior to packaging) stimulated RIGI, but not MDA5, using knockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…For HIV, recent studies suggest that such newly transcribed HIV RNA can be differentiated from cellular RNAs by its high degree of secondary structure, including stem-loops or panhandles and other modifications. Therefore, HIV RNA can be differentially sensed by RIGI in the 5= and 3= untranslated regions, including the TAR stem-loop, which are likely to be recognized by RIGI and are probably more exposed in monomers than dimers (46,47). Solis et al (30) showed that both purified monomeric and, to a lesser extent, dimeric genomic RNA (which is transcribed from cDNA and exposed in the cytoplasm prior to packaging) stimulated RIGI, but not MDA5, using knockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…Cells are equipped with a plethora of pattern recognition receptors (PRRs) that induce an antiviral immune response upon sensing of patterns associated with viral infection. Among them are cytosolic receptors such as cGAS, PQBP1, IFI16, and RIG-I recognizing viral DNA or RNA species, as well as restriction factors such as TRIM5α and Tetherin that sense viral capsids or budding virions, respectively [ 1 ]. The signaling cascades initiated by these receptors converge in the activation of a few key transcription factors ( i .…”
Section: Introductionmentioning
confidence: 99%
“…e . NF-κB, IRF3 and IRF7), which induce the expression of interferons (IFNs) and other antiviral factors [ 1 , 2 ]. HIV and related simian lentiviruses have evolved sophisticated means to evade these innate sensing pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses, which have coevolved with their host, develop strategies to counteract the signaling cascades of the innate immune system and ensure their replication. Recently, several reviews were published, describing the innate immune evasion strategies of individual viruses or virus families, such as influenza virus (2,3), Phleboviruses (4), Herpes viruses (5)(6)(7), Coronaviruses severe acute respiratory syndrome (SARS) and middle east respiratory syndrome (MERS) (8), human immunodeficiency virus (HIV) (9,10), as well as multiple RNA viruses (11,12). Moreover, there are recent articles that review how viruses prevent detection by pathogen recognition receptors (PRRs) (13,14) and how viruses modulate innate immune signaling by use of viral deubiquitinases (15).…”
mentioning
confidence: 99%